Behcet's disease in acquired immune deficiency syndrome. (2016) - Siddiqui, Beenish; Fernandes, Denise; Chaucer, Benjamin; Chevenon, Marie; Nandi, Minesh; Saverimuttu, Jessie; Nfonoyim, Jay
Abstract: HIV/AIDS patients often present with orogenital ulcers. In the immunocompromised patient diagnosis of these ulcers pose a challenge, as there is a myriad of etiologies. We present a case of an HIV/AIDS patient with recurrent orogenital aphthosis that was confirmed to have concomitant diagnosis of Behcet's disease. Proper awareness of the causes of these ulcers is essential for prompt and effective treatment. While rare causes may be at the bottom of a differential list in an immunocompetent host, when HIV/AIDS is involved these rare causes often percolate to the top.